2014
DOI: 10.1167/iovs.13-13407
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Induced Differentiation of Human Meibomian Gland Epithelial Cells

Abstract: Overall, our findings indicate that immortalized human meibomian gland epithelial cells may serve as an ideal preclinical model to identify factors that control cellular differentiation in the meibomian gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 55 publications
1
52
1
Order By: Relevance
“…Such reversibility has also been observed in primary human corneal cells 30, indicating that the immortalized HMGECs share characteristics of primary cells. Indeed, we have previously found that many of the genetic responses of immortalized HMGECs are the same as those of primary HMGECs 18. These findings suggest that this MG cell line, which features a normal karyotype, represents an appropriate model in vitro to study HMGEC dynamics 16.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Such reversibility has also been observed in primary human corneal cells 30, indicating that the immortalized HMGECs share characteristics of primary cells. Indeed, we have previously found that many of the genetic responses of immortalized HMGECs are the same as those of primary HMGECs 18. These findings suggest that this MG cell line, which features a normal karyotype, represents an appropriate model in vitro to study HMGEC dynamics 16.…”
Section: Discussionmentioning
confidence: 67%
“…After reaching 60%–70% confluence, cells were placed for varying intervals in one of the following media: KSFM alone, PM, or serum‐containing medium composed of 10% fetal bovine serum (Thermo Fisher Scientific) in equal volumes of Dulbecco's modified Eagle's medium and Ham's F12 (differentiation medium [DM], Mediatech, Inc., a Corning Subsidiary, Manassas, VA) to induce cell differentiation 18. To accelerate differentiation of HMGECs, 10 μg/mL azithromycin (AZM; Santa Cruz Biotechnology, Dallas, TX) was added to the DM 19.…”
Section: Methodsmentioning
confidence: 99%
“…However, there have been no reports so far that would demonstrate that MG-derived cell cultures in vitro were able to produce lipids that would be identical (or even similar) to the mature MG secretions described in this paper. Indeed, the reported lipidomes of the cell cultures were much closer to the regular lipid profiles of non-differentiated epithelial cells that are enriched with PL and TAG, but lack WE, CE and other typical components of meibum [7476]. Thus, it remains unknown what regulatory factors are responsible for triggering meibogenesis, which our current mechanistic approach (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…14 Previous studies, including some from our group, showed the functional influence of cultivation conditions, 15,16 neurotransmitters, 17,18 growth factors, 19,20 x-3 fatty acids, 21 sex hormones, 22,23 and pharmacologic substances 24 on HMGEC. However, all of these studies rely on 2D cell culture conditions or limited animal experiments.…”
mentioning
confidence: 94%